Comparison of surgical versus medical therapy in the patients with malignant cerebral infarctions-A retrospective study from Southern India - Karkal Ravishankar Naik (Journal of the Scientific Society, 2016)
Introduction: Large hemispheric infarctions secondary to occlusion of middle cerebral artery (MCA) are termed "malignant MCA territory infarctions" due to high mortality and morbidity resulting from large infarction volume and herniation. Decompressive craniectomy has been found to improve the outcome in these patients. Objectives: To evaluate the outcome with surgical management in comparison with conservative management in the treatment of malignant MCA territory infarction. Materials and Methods: The patients with malignant MCA territory infarction admitted from August 2009 to January 2014 were included in the study. Clinical, laboratory, and radiological data were collected from hospital records. The outcome was measured at discharge and at last follow-up. Results: Out of 692 patients with MCA territory infarctions 66 had malignant MCA infarctions (9.53%). Among them 31 underwent surgical decompression (age 45.77 ± 15.33 years) and 35 were medically treated (age 56.11 ± 14.99 years). There was no significant difference in the sex ratio, comorbidities, blood sugars, incidence of hemorrhagic transformation, and herniation between the two groups. Admission Glasgow coma scale (GCS) was higher in surgically treated patients. In-hospital mortality among the patients in the surgical group was 19.35% and in the medical group was 17.34%. Thirteen patients were lost for follow-up. In the remaining 53 patients, there was statistically nonsignificant increase in the death and severe disability in medically treated patients (75% and 78.5%, respectively) in comparison with Surgically treated patients (52% and 68%, respectively). Conclusion: Decompressive craniectomy can improve long-term survival and functional outcome in the patients with malignant MCA territory infarctions.